Research progress on the role of biomechanical clues in the progression of lung cancer - Gong, Fengying; Zhang, Qiang; Fan, Qin; Qu, Rongmei; Wang, Congrong; Yang, Ting; Fan, Tingyu; Lv, Ying; Dai, Jingxing (Frontiers in Cell and Developmental Biology, 2025)
Cells in mammals perceive and react to the mechanical properties of their surrounding environment. Disease progression is frequently linked to dynamic changes in cellular and tissue mechanics. Mechanical responses have been investigated in a broad range of pathological states, notably viral and bacterial infections, inflammation, cystic fibrosis, and tumorigenesis. The lung is an inherently mechanosensitive organ. As such, it is subjected to tremendous mechanical forces. Evidence suggests that lung tumors are subjected to and react to active and passive forces that are critical for their initiation, differentiation, migration, and effector functions, as well as those of their extracellular matrix. This review discusses the latest advances in the investigation of the mechanics of lung cancer cells, focusing on the effects of mechanical signals from tumor microenvironment on tumor cell metabolism and tumor aggressiveness. Investigating the biological impacts of stress and stiffness alterations in lung cancer cells and their associated extracellular matrix can enhance our understanding the pathogenesis of lung cancer and offer novel insights for future therapeutic strategies.